Traditional Uses and Local Knowledge of Lontar (Borassus flabellifer L.) in Pamekasan, Madura - Lukman Baihaqi; Wisanti; Kristinawati Putri, Eva (LenteraBio : Berkala Ilmiah Biologi, 2022)
Lontar (Borassus flabellifer L.) is a species of the Palmae (areca) family that is commonly found in Indonesia. Lontar has many traditional benefits for people in Indonesia. This study aimed to reveal the traditional uses of lontar in the Pamekasan community, determine the use value of the lontar, and describe the local knowledge of the Pamekasan community in terms of the importance of its organ. This research was a descriptive study with observation and survey techniques which was carried out in three villages in Pamekasan. Data were collected through interviews using semi-structured instruments to key informants and respondents about the use of lontar. Five key informants were determined based on purposive sampling consisting of three village elders, a lontar craftsman and a lontar cultivator. Respondents amounted to 25 people per village. Local knowledge data were analyzed using use value and organ importance value (weighting value). The results showed that the plant parts used by the Pamekasan community traditionally were leaves, stems, bark, fruit, flowers, roots. Local knowledge of the Pamekasan community showed that the important value of the lontar plant including their flowers, leaves and fruit. The highest use value of lontar in Pamekasan reached by the usage as beverage ingredients (77%). The traditional use of lontar was by drying, drying, weaving, slicing, tapping, cooking.